PERMAINAN LUDO SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA SEKOLAH DASAR - Visca Elya Anastasya; Ristiyani Ristiyani; Nur Fajrie (WASIS : Jurnal Ilmiah Pendidikan, 2021)
The purpose of this study iwas to analyze the ludo game as an effort to improve the creative thinking skills of elementary school students. Research conducted using classroom action research. The study was conducted in two cycles. The subject of research is the fifth grade students of SDN Jakenan with 24 students. Data colectiontechniques used are observation, interviews, evaluation test and documentation. The validity of the data used expert judgment techniques. Analysis of the data used is the analisysis of qualitative and quantitative data.Based on the aspect of creative thinking the value in the cycle I obtained an average of 76,79 in Indonesia content and IPS content an average of 79,37. Cycle II the value of Indonesian Content gained an average of 81 and the IPS content obtained an average value of 86,37. Whereas the ludo game obtained an average in cycle I of 74% and cycle II gained an average of 82%.